(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Osteocalcin (OC) and its effect on insulin resistance in animals have been studied and demonstrated. But, the same is yet to be established in humans. Moreover, the association of Gestational Diabetes Mellitus (GDM) with serum Osteocalcin (OC) levels hasn’t been studied much and hence, is an area of scope for research. This study is aimed at assessing the difference between serum OC levels in non-diabetic pregnant women (Group I – Controls) and women diagnosed with GDM (Group II – Cases) and determine whether they can be used in early prediction of GDM. Methods: A thorough and systematic search of PUBMED and SCOPUS databases was done to identify relevant articles, using the keywords Osteocalcin, pregnancy, diabetes and gestational diabetes. Studies which had included atleast 10 study participants per group and had measured serum OC levels in various forms viz., undercarboxylated Osteocalcin (ucOC), N terminal Mid fragment Osteocalcin (N MID OC) and total Osteocalcin (tOC) were considered relevant. Out of 45 studies, 9 studies were selected for the present study. Results: There was no significant difference in the mean ucOC and N MID OC levels between the GDM and nondiabetic controls, whereas, a significant difference was found in the tOC levels between the two groups. Conclusion: Thus, this meta-analysis shows that tOC may be used as potential marker for GDM rather than ucOC and N MID OC.